THE EFFECT OF SKILL AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT. PT. WAHYU RINTIYANI PERKASA BANGKINANG - Fiqih Anjani; Zamhir Basem; Yusup Yusup; Adi Setiawan (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to determine the effect of skills and work environment simultaneously and partially on employee performance at PT. Wahyu Rintiyani Perkasa Bangkinang. The population in this study were all employees at PT. Wahyu Rintiyani Perkasa Bangkinang, totaling 52 employees. Determination of the sample in this study using the saturated census method so that the number of samples in this study were 52 respondents. Data analysis was carried out using multiple linear regression models. Based on the results of the simultaneous test, the skill and work environment variables have a significant effect on the performance of employees at PT. Wahyu Rintiyani Perkasa Bangkinang. Meanwhile, based on the partial test results, the skill and work environment variables have a significant effect on employee performance at PT. Wahyu Rintiyani Perkasa Bangkinang. The close relationship that occurs between the skill and work environment variables on employee performance at PT. Wahyu Rintiyani Perkasa Bangkinang is very strong with a correlation coefficient (R) of 87.4%. Meanwhile, the contribution of skill and work environment variables to employee performance at PT. Wahyu Rintiyani Perkasa Bangkinang is 76.3% while the remaining 23.7% is influenced by other variables not examined in the study.